Development Exercise Model In Butterfly Swimming For Athletesin The Age Group 11-13 Years Based on Drill Throught Android App - Gani, Ruslan Abdul; Tangkudung, James; Dlis, Firmansyah (Journal of Education, Health and Sport, 2019)
The aim of this study is to develop and produce an exercise model on butterfly stroke swimming skill for athletes aged 11-13 years. The method used in this study refers to the model development method or Research and Development (R&D) based on the 10 steps of development proposed by Borg and Gall. The percentage of the results of trial on small group is 82.06% while the percentage of the results of trial on large group is 84.35%. The results of the study, obtained through the effectiveness test, found t-calculate 16.66 > t-table 2.02 in the experimental group and t-calculate 9.996 > t-table 2.02 in the control group. Thus, the study concluded that there is the effectiveness of the results on butterfly stroke swimming skill for athletes in the age group of 11-13 years by the use of drill-based exercise through the android app.